Prevalence of Counselling Alliance Type Preferences Across Two Samples - Bedi, Robinder P.; Duff, Carlton T. (Canadian Journal of Counselling and Psychotherapy, 2009)
A cross-sectional survey was conducted across two samples of counselling clients to estimate the prevalence of two sets of counselling alliance type preferences: (a) nurturant, insight-oriented, or collaborative alliance (Bachelor, 1995); and (b) personal or professional alliance (Mohr & Woodhouse, 2000, 2001). Results indicated that participants generally preferred an insight-oriented alliance type over a nurturant one, and in one sample, a collaborative type over a nurturant one. In addition, participants in both samples preferred a personal or professional alliance about equally. These findings support the existence of tangible alliance type preferences across clients.